Parents' perspective on the physical and socio-emotional changes of school-aged children in dance programs - Lagmay, Camille Isabel T.; Limjap, Lara Cristina M.; Quijano, Maria Lourdes M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT This study was conducted primarily to determine the physical and socio-emotional changes of school-aged children who are currently in a dance program from the perspective of the parents. The aim of the study is to provide other professionals, including parents, information on the influences of dance, specifically, in the development of children in the physical and socio-emotional aspect. Information from which were obtained through the interview of 30 different parents - 15 mothers and 15 fathers, all with children aged 6-12 years old who have been enrolled at an earlier age and are at present in a dance program. The study accomplished to introduce the themes that arose in the results of the research upon thematic analysis. These themes were structured in such a way that the obtained results may be distinguished at a more general understanding. The changes in the physical aspect were categorized into the following themes: Improved Skills, New Skills Acquired, Improved Body Function, and Change in Body Appearance. On the other hand, the changes in the socio-emotional aspect were organized into the following themes: Self-Expression, Sociability, and Self-Reliance. A big portion of this study may be of use to a variety of professionals that involve interaction or relation with children, and especially the parents who play an integral part in a child's life. These professionals may choose to control, improve, and/or maintain the development of a child, not only in the aspect of dance, but in all other different aspects that influence a child's development as well.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Child development -- Philippines; Dance for children -- Philippines